Calcium peroxide alleviates the waterlogging stress of rapeseed by improving root growth status in a rice-rape rotation field - Wang, Zhiyuan; Han, Yongliang; Luo, Shang; Rong, Xiangmin; Song, Haixing; Jiang, Na; Li, Changwei; Yang, Lan (Frontiers in Plant Science, 2022)
Waterlogging stress has a negative influence on agricultural production, particularly for rapeseed yield in a rice-rape rotation field. To alleviate the profound impacts of waterlogging stress on rapeseed production, a new fertilization with calcium peroxide (CaO2) was proposed. In this field experiment, with the conventional rape (Brassica napus L.) variety fengyou958 (FY958) and early maturing rape variety xiangyou420 (XY420) as materials, waterlogging was imposed from the bud to flowering stage, and three supplies of CaO2 (0, C1 for the 594 kg hm-2 and C2 for the 864 kg hm-2) were added as basal fertilizer. The results showed that CaO2 significantly reduced the accumulation of fermentation products in roots, and alleviated the peroxidation of leaves. The reduced waterlogging stress promoted the root vigor and agronomic characters, such as branches, plant height and stem diameter, accelerated dry matter and nutrients accumulation, and resulting in 22.7 % (C1) to 232.8 % (C2) higher grain yields in XY420, and 112.4 % (C1) to 291.8 % (C2) higher grain yields in FY958, respectively. In conclusion, 594 kg hm-2 to 864 kg hm-2 CaO2 application restored the growth of waterlogged rapeseed leaves, and reduced the anaerobic intensity of root, which enhanced the resistance of plants to waterlogging, and improved crop productivity. In a certain range, the higher CaO2 application, the more the yield. This study provides a valid method to prevent damage from flooding in crop fields.